2006
DOI: 10.1182/blood-2005-08-3374
|View full text |Cite
|
Sign up to set email alerts
|

Graft rejection after unrelated donor hematopoietic stem cell transplantation for thalassemia is associated with nonpermissive HLA-DPB1 disparity in host-versus-graft direction

Abstract: The success of allogeneic hematopoietic stem cell transplantation (HSCT) from matched unrelated donors (UDs) for ␤-thalassemia may be hampered by the occurrence of graft rejection. Here, we show that the rate of this complication can be reduced by selecting 5-loci HLAmatched donors without nonpermissive mismatches at HLA-DPB1, defined according to an algorithm previously described and based on principles of central T-cell tolerance. Seventy-two consecutive patients and their UDs, prospectively selected for mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 36 publications
1
96
0
1
Order By: Relevance
“…Fleischhauer et al reported an increased risk of graft failure with the presence of nonpermissive HLA-DPB1 mismatches, in a group of unrelated ASCT for betathalassemia patients. 15 Interestingly there was not increased risk of GVHD and decreased OS in non permissive HLA-DPB1 disparities in this study population. Later, Shaw et al once again analyzed the clinical importance of HLA-DPB1 in unrelated ASCT.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Fleischhauer et al reported an increased risk of graft failure with the presence of nonpermissive HLA-DPB1 mismatches, in a group of unrelated ASCT for betathalassemia patients. 15 Interestingly there was not increased risk of GVHD and decreased OS in non permissive HLA-DPB1 disparities in this study population. Later, Shaw et al once again analyzed the clinical importance of HLA-DPB1 in unrelated ASCT.…”
Section: Discussionmentioning
confidence: 49%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study by Loiseau et al reported increased frequency of severe aGVHD and poorer survival in two HLA-DP incompatibilities in a group of unrelated ASCT patients. 10 In this study they were not able show a significant relationship between HLA-DP mismatches and disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Although Fleischhauer et al demonstrated that GR after UD-HSCT for thalassemia was associated with nonpermissive HLA-DPB1 disparities in the hostversus-graft direction, 23 the importance of HLA-DPB1 donorrecipient matching remains debatable. In the present study, GR 24 The use of PBSCT was not associated with a significantly increased risk of either acute or chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…15 This algorithm, based on the identification of an immunogenic T-cell epitope shared by a defined subset of HLA-DBP1 alleles, which, if expressed by self-HLA-DP molecules protects from mounting a response against allogeneic HLA-DP antigens carrying the epitope, 15,16 proved also to predict the occurrence of graft failure in children with thalassemia major transplanted with BM cells from an unrelated volunteer. 17 Thus, at least in some groups of patients transplanted from an unrelated volunteer, the incidence of immune complications (namely GvHD and graft failure) can be reduced by appropriate selection of the donor, taking into account the functional rules of immune genetics. Besides HLA compatibility, several other patient-, donor-, disease-and transplant-related variables have been reported to influence the outcome of children given an allogeneic HSCT from an unrelated donor.…”
Section: Unrelated Bm Donorsmentioning
confidence: 99%